Inovasi Sistem Kontrol Akses Gerbang Kantor Pemerintahan Berbasis Teknologi Multisensor dan Deteksi Plat Nomor Kendaraan - Masril, Mardhiah; Ondra Eka Putra; Hasri Awal; Billy Hendrik (LPPM-ITEBA, 2024)
Technological advances are developing rapidly at this time, the need for efficiency, security and automation in the office environment has become a top priority. One innovation that answers this need is technology for office gates, the need for a more sophisticated and efficient access control system is increasingly urgent. The problem that occurs, namely intrusions outside working hours, means that unknown individuals can easily enter the office area without permission. Additionally, cases involving lost employee ID cards, which were used by others to access designated areas, underscore the need for identification systems that are more secure and difficult to abuse. The office gate security system utilizes Webcam Camera input, RFID Reader, Fingerprint Sensor, Ultrasonic and Esp8266, Web, Servo, LED, LCD and Buzzer output. The Webcam camera can take pictures and save them on the web and the RFID Reader detects E-KTP, the Fingerprint sensor detects fingerprints and then the LCD displays information that registration is successful. This tool is processed with an Arduino Mega 2560 microcontroller as a connection.